2012
DOI: 10.1111/j.1523-5378.2011.00930.x
|View full text |Cite
|
Sign up to set email alerts
|

Fragmented CagA Protein is Highly Immunoreactive in Japanese Patients

Abstract: Background:  High‐molecular‐weight cell‐associated proteins (HM‐CAP) assay is the most popular serological immunoassay worldwide and has been developed from US isolates as the antigens. The accuracy is reduced when the sera are from adults and children in East Asia including Japan. To overcome the reduced accuracy, an enzyme immunoassay using Japanese strain–derived HM‐CAP (JHM‐CAP) was developed, in which the antigens were prepared by exactly the same procedure as HM‐CAP. The performance of JHM‐CAP was better… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…As the H. pylori strains differ worldwide, the performance of serological kits show high variation in populations from different geographical areas. Antibody tests evaluated in the East may not be appropriate for clinical diagnosis in the West [1,14,15]. Use of pooled antigen preparations might overcome this limitation.…”
Section: Serologymentioning
confidence: 93%
“…As the H. pylori strains differ worldwide, the performance of serological kits show high variation in populations from different geographical areas. Antibody tests evaluated in the East may not be appropriate for clinical diagnosis in the West [1,14,15]. Use of pooled antigen preparations might overcome this limitation.…”
Section: Serologymentioning
confidence: 93%
“…104 Additionally, sera from Japanese patients was highly reactive to a 100 kDa fragment of CagA that was isolated from Japanese clinical isolates using a high-molecular weight cell-associated proteins (HM-CAP) assay. 118 In contrast, when this assay was performed using isolates from the United States, a larger CagA fragment that was not as reactive as the Japanese HM-CAP fragment was generated. 118 These different sized cleavage products suggest that there may also be structural differences in the various CagA proteins.…”
Section: Cagamentioning
confidence: 99%
“…118 In contrast, when this assay was performed using isolates from the United States, a larger CagA fragment that was not as reactive as the Japanese HM-CAP fragment was generated. 118 These different sized cleavage products suggest that there may also be structural differences in the various CagA proteins. 118 Of note, these proposed structural differences do not appear to alter the stability of CagA within the host cell since CagA EPIYA-ABD and CagA EPIYA-ABCCC do not exhibit a statistically significant difference in their half-lives.…”
Section: Cagamentioning
confidence: 99%
See 1 more Smart Citation
“…Serological diagnosis of H. pylori for children, however, has been problematic for Japanese children; we found that the diagnostic performance of an enzyme immune assay (EIA) kit based on Japanese strain-derived high-molecular-weight cell-associated protein (JHM-CAP kit) was much better than that based on U.S. strain-derived high-molecular-weight cell-associated protein (HM-CAP kit) [17], although the performances of the two kits for adult populations were not much different [18]. Such a clear difference between the two kits for diagnosis of H. pylori infection in Japanese children was shown to be attributed to the 100-kDa antigen protein contained only in JHM-CAP, which was later identified as a fragmented CagA protein [19]. Intriguingly, 100-kDa CagA fragments were also identified in gastric cells and phagocytic cells after infection by western H. pylori strain [20], [21].…”
Section: Introductionmentioning
confidence: 99%